Correlation Between Endometrial Thickness By Ultrasonography and Histopathology in Abnormal Uterine Bleeding - G, Sujana; Gerorge, Vivek; Chandramohan, Aswathy; Vasudevan, Sheela; Anthony, Divya (Annals of Pathology and Laboratory Medicine, 2020)
Background : Abnormal uterine bleeding (AUB) is the most common presenting complaint of patients in Gynaecology Outpatient department. Early diagnosis of endometrial hyperplasia through ultrasongraphic measurement of endometrial thickness and definite diagnosis by histopathologic examination will help the clinicians to give appropriate treatment to the patients. The objective of this study was to correlate the histopathology findings in abnormal uterine bleeding with endometrial thickness by ultrasonography. Methods : This was a prospective study done from Nov 2016 to June 2018.A total of 382 cases of AUB presenting above 40 years of age were included. Endometrial thickness was measured by ultrasonography. Histopathological findings were studied and compared with the endometrial thickness. Statistical analysis were done using chi square test. Results : A total of 382 cases were analysed. Maximum number of cases were from peri menopausal age group (68.32%). Majority of the cases were due to non organic causes(85.34%). 46.86% of patients had endometrial thickness of 5-10mm followed by endometrial thickness of 11-15mm in 39.01%. Disordered proliferative endometrium was the most common pattern (38.34%) in our study followed by secretory endometrium (35.58%) and menstrual endometrium (18.71%). These findings were found to be statistically significant. Conclusion : A thorough histopathological work up and clinical correlation is mandatory in cases of abnormal uterine bleeding above 40 years to find out organic lesions. Careful screening can detect precursor lesions like endometrial hyperplasia and early cases of endometrial carcinoma which has excellent prognosis and it will help in further management.